Challenges in the management of oral ulceration in elderly patients - Nanan Nur'aeny (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Oral ulceration can be experienced by anyone, including those who are elderly. Various trigger factors can occur in elderly patient, but the main thing to consider is the degenerative factors that affect the occurrence of some medical problems. Handling oral ulceration in elderly patients should be done carefully and holistically otherwise the improvement is only temporary and can reappear or even be worse. Purpose: In this paper we will discuss two different case reports of elderly female patients and both having some oral ulceration. Cases: First case of recurrent oral ulceration experienced by 58 years old patient, and second case is concerning a 77 years old patient with chronic oral ulceration and also having some medical problems. Aphthous like ulcers (ALU) is a diagnosis for recurrent oral ulceration associated with systemic condition, and usually started after adolescent age. Elderly or geriatric condition itself is a special condition that contribute to the degree of a disease. Cases management: Both patients given non pharmacology and pharmacology therapies. The non pharmacology therapy includes communication, information, and education, also oral hygiene instruction. Steroid as anti-inflammatory drugs had an important role in healing process, beside other medication. Conclusion: Oral ulceration in elderly patients with or without a medical problems becomes a challenging thing to handle due to the complexity of their condition. As a dentist we have more careful to arrange the treatment plans for elderly patients when combine with some therapy related systemic disease.